2016
DOI: 10.4239/wjd.v7.i19.554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depression and diabetes in pregnancy: A systematic review

Abstract: AIMTo systematically review the literature on women with both diabetes in pregnancy (DIP) and depression during or after pregnancy.METHODSIn this systematic literature review, PubMed/MEDLINE and EMBASE were searched (13 November 2015) using terms for diabetes (type 1, type 2, or gestational), depression, and pregnancy (no language or date restrictions). Publications that reported on women who had both DIP (any type) and depression or depressive symptoms before, during, or within one year after pregnancy were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 73 publications
(302 reference statements)
1
40
2
Order By: Relevance
“…The high variability of the results is due to differences among populations and when the data were collected, in addition to the factors that were mentioned above [11]. Furthermore, no specific studies were found on GDM and depression in the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…The high variability of the results is due to differences among populations and when the data were collected, in addition to the factors that were mentioned above [11]. Furthermore, no specific studies were found on GDM and depression in the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patient comorbidities assessed were predictive of outcome in our univariate analyses, although small study size may have prevented several (depression, substance use disorder, and complicated diabetes) from reaching statistical significance. Depression and diabetes in pregnancy have been studied extensively without clear consensus about their associative relationship, and our study again underscores a need for specific research into this area [24]. The link between these and alcohol/substance abuse, which together have been described as a comorbid “triad”, are certainly plausible from a socioecological and biological perspective [25].…”
Section: Discussionmentioning
confidence: 79%
“…There are three main pathways to cell apoptosis which are: (1). DNA methylation through ion carbonium formation (CH 3+ ) can cause activation from poly ADP-ribosesynthase enzyme as part of the cellular repairing mechanism and as result, there is decrease of Nicotinamide Adenid Dinukeotida(NAD + ); (2). NO Production; (3).…”
Section: Discussionmentioning
confidence: 99%
“…in the United States prevalence of GDM increased by 56%. 2 After the baby is born, usually GDM disappear. The Oral Glucose Tolerance Test (OGTT) were conducted for six weeks after delivery to make sure that the blood glucose is back to normal.…”
Section: Introductionmentioning
confidence: 99%